Guess the Score, fostering collective intelligence in the class - Josep M. Monguet; Jaime Meza (European Alliance for Innovation (EAI), 2015)
This paper proposes the use of serious games as a tool to enhance collective intelligence of undergraduate and graduate students. The development of social skills of individuals in a group is related to the performance of the collective intelligence of the group manifested through the shared and collaborative development of intellectual tasks [1]. Guess the Score GS, is a serious game implemented by means of an online tool, created to foster the development, collaboration and engagement of students. It's has been designed with the intention of facilitating the development of individual's social skills in a group in order to promote education of collective intelligence. This paper concludes that the design of learning activities using serious games as a support tool in education, generate awareness about of utilities of gaming in the collective learning environment and the fostering of collective intelligence education.